Factors influencing teachers' professional competence development - Grangeat, Michel [Verfasser]; Gray, Peter [Verfasser] (My University, 2007)
Der vorliegende Beitrag möchte einen Beitrag zur Verbesserung des Verständnisses und des Wissens zur Kompetenzentwicklung von Lehrern leisten. Es werden mehrere Modelle aus dem industriellen Kontext analysiert und auf dieser Basis ein Rahmen mit verschiedenen relevanten Komponenten der Arbeitsumgebung von Lehrern entwickelt. Die Daten basieren auf 60 Interviews. Ein wesentliches Ergebnis ist, dass der Austausch zwischen Lehrern und Schulpartnerschaften ein zentraler Faktor für die Verbesserung der Lehrkonzepte von Lehrern darstellen. (BIBB-Doku)

"This article aims to increase understanding and knowledge concerning teachers' competence enhancement. Models used in industrial contexts are analysed in order to elaborate a framework relevant to understand teachers' learning. This specifies components of the work environment that are mobilised by teachers in order to achieve their goals. It is used to identify ways in which teachers in France manage to improve their practice despite being involved in complex and difficult situations. The data come from 60 interviews. The results highlight the effects of the organisation of the collective work situations: spurring exchanges amongst teachers and school partners appears to be a main factor for improving teachers' conceptions about teaching. Some ideas are outlined for constructing new continuing professional development programmes and studying their effects." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2.3 Lehrer; I 2.2.1 Westeuropa; Kompetenzentwicklung; Lehrer; Frankreich